Microdilution Broth Method for Determination of Minimum Inhibitors Concentration of Thyme and Clove Essential Oil against Methicillin Resistant Staphylococcus aureus - Ghufran Jebur Shamkhi (Journal of Global Pharma Technology, 2019)
The essential oil extracted from air-dried Thyme leaves (Thyme vulgaris) and Clove buds (Eugenia caryophyllata) by distillation method. The results showed lowest MICs value when exposure to natural bioactive products and demonstrated high activity againstMRSA isolates. The MICs value of Thyme and Clove EOs and the standards (thymol and eugenol) were ranged from (0.195-0.39) μg/ml, (0.39-0.78) μg/ml and (0.097-0.048) μg/ml respectively, to enhance microdilution method described in our study improved through adding redox indicator which was Resazurin dye.Keywords: Clove Essential Oil; Inhibitors; Staphylococcus aureus.